Plant and agricultural biotechnology achievements, prospects and perceptions - Sasson, Albert (Coordinación de Ciencia Y Tecnología de Nuevo León, México UNU-IAS BioEuroLatina, 2006)
This is therefore a valuable contribution to the state of knowledge of agricultural biotechnology and to the efforts aimed at raising awareness among all stakeholders and informing university students, teachers and civil society about the implications and prospects of this major sector of biotechnology.